The Effectiveness of Interactive Module Based on Lectora™ to Improve Secondary School Students’ Spatial Ability - Tika Septia; Sofia Edriati; Merina Pratiwi (SEAMEO Regional Centre for QITEP in Mathematics, 2017)
Polyhedral geometry is a topic that requires students’ spatial ability. The study aims at evaluating the effectiveness of the implementation of the interactive module based on Lectora™ for students. Action research was adopted for this study. This research consisted of two cycles where each followed the steps: plan, implementation, observation, and reflection. The subjects of this study was students Grade 8 of SMP Taman Siswa. In general, learning is said to be effective if at least 85% of students pass the test. The findings show that 75% of the students in cycle I got maximum test score and in cycle II the percentage increases to 87.5%.